PENGARUH EFIKASI DIRI DAN TEAM WORK TERHADAP KINERJA GURU DENGAN INOVASI SEBAGAI VARIABEL INTERVENING PADA SMA DAN SMK DI SANGATTA - Mulianto Doeng; Tri Gunarti Ningrum; Nurlianti; Rizkiawan (Program Studi Manajemen, 2025)
This study aims to analyze the effect of self-efficacy and teamwork on teacher performance with innovation as an intervening variable in senior high schools and vocational high schools in Sangatta. This research employed an associative quantitative approach. The population consisted of 338 teachers, while the sample consisted of 183 respondents determined using the Slovin formula with a 5% error rate and proportional random sampling. Data were collected using a 1-5 Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that self-efficacy and teamwork do not significantly affect innovation. However, self-efficacy, teamwork, and innovation have positive and significant effects on teacher performance. Innovation does not mediate the effect of self-efficacy on teacher performance, but it mediates the effect of teamwork on teacher performance. The R-square values of innovation (0.733) and teacher performance (0.832) indicate strong explanatory power. These findings suggest that improving teacher performance in Sangatta is more effective when supported by stronger self-efficacy, productive teamwork, and structured instructional innovation.